Українська шляхта між польським та українським етносами - Балушок, В. (Народна творчість та етнографія, 2007)
Appearance and existence of the Ukrainian gentry relates to the traditions of Polish political culture, so during the whole period of its life it was between the Ukrainian and the Polish ethnic groups. Polanisation of the Ukrainian gentry begins at the date when some of the Ukrainian territories become a part of Poland and strengthens after Cossack revolution in the middle and at the end of the 16th century. Especially this process becomes effective at the beginning of the 18th century when a great part of gentry from other Polish lands migrates to Pravoberezhia (right-banked Ukraine). Nevertheless, having captured upper class and partially middle class of the Ukrainian gentry, polanisation mainly influenced consciousness and less religion of the lower class of the Ukrainian gentry. As for ethnoculture and language local gentry was mostly Ukrainian and it assimilated numerous Polish gentlemen-immigrants.